The Influence of Waiting Staff on Customer Retention in Two-Star Hotels in Takoradi Metropolis - Spio-Kwofie, Adelaide; Deh, Janet; Amoah, Hannah (Eximia, 2025)
The study’s primary objective was to examine the impact of waitstaff on customer retention in two-star hotels in the Takoradi Metropolis. The study’s goals were to identify the role of the hotel waiting staff in service delivery, to determine the factors affecting customer retention, and to examine measures employed to promote customer retention in two-star hotels in Takoradi. A survey research design was employed for the study. The study population was five (5) waiting staff from twelve (12) two-star hotels in Takoradi, which was made up of sixty (60) respondents. A random sampling technique and a questionnaire for data collection was used for the study. The study found that most waiting staff take orders, welcome customers, and lead them to their seats. The findings of the study further revealed that employees are empowered by management to interact with customers to meet their needs. It was evident from the study that when customers are satisfied with the services provided by the waiter, and experience a good atmosphere and waiting time, they return to the hotel. The study concludes that the role of hotel waiting staff in service delivery in two-star hotels significantly affects hotel customer retention. The study recommends that two-star hotels should organise regular training for their waiters to enable them to gain knowledge in providing quality waiting service to customers. This will encourage customers to patronise the hotel, thus leading to customer retention.